Clinical Outcome of Intralesional Corticosteroid Therapy in Management of Cutaneous Hemangiomas in Children (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction:Hemangioma are benign neoplasms of the vasculature of infants and children and are classified into two major types, (tumors and vascular malformations). These lesions, often referred to as infantile hemangiomas (IH), are considered to be the most common tumors of infancy.Objectives:To evaluate the efficacy of intralesional triamcinolone in enhancing regression in infantile cutaneous hemangiomas.Materials and Methods:In this clinical trial all patients’ age, sex, presence of any complications, site and size of lesion and the percentage of regression after steroid injection were evaluated. The patients were treated with local injection of diluted triamcinolone (40 mg) with 5 ml normal saline in a dose of 3-5 mg/kg. The injection was given every 4-6 weeks. The number of injections varied from two to six. Parameters used for grading the responses of IH after treatment are excellent response, Good response, Poor response, No response.Results:Out of 162 patients 88(54.32%) were less than 1 year of age among them 60(68.18%) showed excellent response. Female patient was 119(73.46%) among them 74(57.98%) showed excellent response. Maximum 85(52.47%) haemangioma was strawberry type and showed better response. Majority 66(40.74%) had facial presentation among them 41(62.12%) showed excellent response. Maximum 110(67.90%) haemangioma was < 3cms in size and response better than other type.  Maximum 68(41.98%) was rapidly growing type tumour and 27(16.67) was bleeding type hemangioma showed better respose.Conclusion:Intralesional injection of triamcinolone is a safe and effective treatment of hemangiomas.  Better response found in female child with size less than 3 cms, rapidly growing tumour, and in strawberry type of hemangioma.JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 137-139